Pengujian Sistem Schedule Planning Produksi Dengan Metode Black Box Testing pada PT. Smartfren Telecom TBK Untuk Pemula - Nur Muhammad Arofiq; Anggita Laksana; Aries Saifudin (Shofanah Media Berkah, 2023)
The existing system faces challenges in effective scheduling, leading to issues such as miscommunication, schedule mismatches, delayed decision-making, and inefficient data processing. The proposed solution involves implementing a desktop application using Delphi programming language and MySQL database to assist production administrators in creating effective and efficient production schedules. The blackbox testing method is employed to test the system's input and output without considering its internal structure. The testing reveals issues including input-output inconsistencies, limitations in processing complex data, and errors in production time calculations. Proposed recommendations include improving input validation, enhancing data processing capabilities, and refining the production time calculation algorithm. The testing and implementation of the Production Schedule Planning Information System aim to improve production effectiveness, minimize schedule mismatches, and enhance customer satisfaction at PT. Smartfren Telecom TBK. The blackbox testing method provides insights into system issues and serves as a basis for necessary improvements.